Durable Nickel‐Iron (Oxy)hydroxide Oxygen Evolution Electrocatalysts through Surface Functionalization with Tetraphenylporphyrin. (18th November 2022) - Kang, Sinwoo; Im, Changbin; Spanos, Ioannis; Ham, Kahyun; Lim, Ahyoun; Jacob, Timo; Schlögl, Robert; Lee, Jaeyoung
Abstract: NiFe‐based oxides are one of the best‐known active oxygen evolution electrocatalysts. Unfortunately, they rapidly lost performance in Fe‐purified KOH during the reaction. Herein, tetraphenylporphyrin (TPP) was loaded on a catalyst/electrolyte interface to alleviate the destabilization of NiFe (oxy)hydroxide. We propose that the degradation occurs primarily due to the release of thermodynamically unstable Fe. TPP acts as a protective layer and suppresses the dissolution of hydrated metal at the catalyst/electrolyte interface. In the electric double layer, the nonpolar TPP layer on the NiFe surface also invigorates the redeposition of the active site, Fe, which leads to prolonging the lifetime of NiFe. The TPP‐coated NiFe was demonstrated in anion exchange membrane water electrolysis, where hydrogen was generated at a rate of 126 L h −1 for 115 h at a 1.41 mV h −1 degradation rate. Consequently, TPP is a promising protective layer that could stabilize oxygen evolution electrocatalysts. Abstract : Fe dissolution is the major deactivation mechanism of Nickel‐Iron (oxy)hydroxide in alkaline oxygen evolution reaction. The water molecule hydrates eluted Fe that easily escape from the double layer. Surface immobilization of tetraphenylporphyrin forms a nonpolar layer that suppresses the penetration of Fe without interrupting the activity. This increases the fraction of Fe redeposition onto the electrode and maintains an active site population.